Direct Dependence on Philo in the Epistle to the Hebrews - Grindheim, Sigurd (Novum Testamentum, 2023)
The near consensus opinion that the author of Hebrews was not directly influenced by Philo needs to be reevaluated. Even though there are no obvious cases of borrowing, the cumulative weight of the evidence indicates a more linear relationship than what may be accounted for by situating them both within Hellenistic Judaism. A number of parallels are sufficiently detailed to suggest direct dependence. These parallels are of a formal character, such as the metaphor of the dagger and the particular use of the terms ὑπόστασις, ἀρχηγός, τελειόω, ἄθλησις, τεχνίτης, and δημιουργός, as well of a material nature, concerning the development of key ideas, such as the eternal nature of the Son, his Melchizedekian high-priesthood, and the perception of the heavenly sanctuary.